Pengaruh Menggunting Pola Transportasi Terhadap Kemampuan Motorik Halus Anak KB Al Karomah Tahun Ajaran 2022-2023 - Wijaya Adi Putra; Sri Laeli Norhayati; Pipit Rika Wijaya (Medan Resource Center, 2023)
The aim of this study is to investigate the impact of altering transportation patterns on the fine motor skills of children at KB AL Karomah in Sumberwringin sub-district, Bondowoso district. This research employs a quantitative approach with a one-group experimental design, focusing on a specific case study. The entire population of 13 individuals was included as participants using a total sampling technique. Data collection involved observation and documentation, and inferential statistical analysis techniques were applied. The results of the hypothesis test indicated that the t-value (10.247) exceeded the critical t-value (2.179). Therefore, following the hypothesis criteria, the null hypothesis (H0) was rejected, and the alternative hypothesis (Ha) was accepted. Thus, it can be concluded that altering transportation patterns has a significant effect on the fine motor skills of children at KB AL Karomah during the 2022-2023 academic year.